Comparative characteristic of eutopic and ectopic endometrial cells in patients with endometriomas - S O Dubrovina; J D Berlim; V Y Mazhugin; L V Krasilnikova; K A Areshuan; V S Gimbut; N S Chirkunova; V Y Tikidzhieva (IP Berlin A.V., 2016)
Objective. To study the morphometric characteristics of eutopic and ectopic endometrial basal cells in patients with endometriosis and without. Material and Methods: The study involved 76 women aged 17 to 42 (average age was 28.97 ± 5.34 years). The main group consisted of 61 women with ovarian endometriosis, control group - 15 patients with infertility, not related to endometriosis. Results. Morphometric evaluation basal endometrial cells revealed that in patients with endometriosis compared with patients without a thickness of 1.25 times lower than the cytoplasmic membrane thickness gland - 1.5 times the thickness of the nuclear membrane - 1.2 times higher average brightness - 1.2 times lower average density - 1.2 times higher. When comparing eutopic and ectopic endometrial cells in endometriosis patients with the following data: the core area is 1.7 times higher in the eutopic endometrial cells, secretory thickness of the cage 2-fold higher in the eutopic endometrial cells, cytoplasmic membrane thickness is 1.3 times higher eutopic endometrial cells, the average density is 1.2 times higher in the cells of ectopic endometrial average brightness 1.19 times higher in eutopic endometrial cells. Conclusion. The results of our work have demonstrated the obvious statistically significant differences in the morphometric analysis of the basal epithelial cells of eutopic between female patients with endometriosis without it. Consequently, not only stem cells from different ectopic foci localization eutopic cells, but the cells themselves and the basement membrane, which are located on mesenchymal stem cells on their morphometric characteristics are distinct and different from endometrial cells without endometriosis patients.